Characterization of BSL6 isolates isolated from honeybee hive and to determine its antibacterial activity - Lenni Fitri; YEKKI YASMIN; FAUZIAH FAUZIAH; DWI ANDRI SEPTIANI; SUHARTONO SUHARTONO (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Fitri L, Yasmin Y, Fauziah, Septiani DA, Suhartono. 2020. Characterization of BSL6 isolates isolated from honeybee hive and to determine its antibacterial activity. Biodiversitas 21: 4859-4865. This study was aimed to characterize BSL6 isolate of bacteria isolated from honeybee hive, and to determine its antimicrobial activity against Staphylococcus aureus and Escherichia coli. In addition, the Minimum Inhibitory Concentration (MIC) value of BSL6 isolate was determined against S. aureus, and content of secondary metabolic compounds was also determined.  Characterization was conducted in this study on the basis of morphological observations, physiological tests, and 16S rDNA. The method used in determining MIC value was completely randomized design (CRD) then analyzed by ANOVA test using SPSS application and followed by Tukey test. The analysis conducted to determine the content of secondary metabolites was descriptive type. The results showed that BSL6 isolate morphologically and physiologically belonged to the genus Bacillus, and 16S rDNA test results showed that the isolate had the highest similarity with Bacillus siamensis strain 64X-5. BSL6 isolate was able to inhibit the growth of S. aureus with inhibition zone diameter of 17.87 mm. MIC value of BSL6 against S. aureus was at a concentration of 12.5%. The content of secondary metabolite compounds from BSL6 extract was saponins.